Prediction of Slamming Occurrence of Catamarans - Grande, Kristoffer (Curtin University, 2002)
In this work the problem of slamming on the cross structure of catamarans is studied. An introduction and overview of the problem is given.Methods for predicting the slamming occurrence of high-speed power catamarans and sailing catamarans are presented. Emphasis is placed ondeveloping methods that are practical to use in order to facilitate prediction of slamming occurrence at the design stage. The methods used consist of three steps: Ship motion prediction, slamming identification and slamming pressurecalculations. Existing linear and non-linear ship motion prediction theories are used for high-speed power catamarans while a new strip theory has been developed specifically for motion prediction of sailing multihulls. Predicted shipmotion results are compared to full-scale experiments, both for high-speed powercatamarans and sailing catamarans. A new direct method for identification of slamming occurrence in the time domain is presented, as well as results using probabilistic methods. A comparison between the two methods is presented.Slamming pressure calculations are done using an existing two dimensional slamming theory and are compared with analytical results. A parametric study is done on two case study ships to investigate the effect of various hullformparameters on the slamming occurrence. The methods and results presented are of use to designers of high-speed power catamarans and sailing catamarans.